Responsiveness Family Law Reform in Indonesia and Tunisia (Study of Post-Divorce Child Custody - Putri, Suci Ramadhani; Anam, Ahmad Gautsul (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
This study aims to explain the development of understanding of child custody after divorce, describe an overview of the provisions of child custody after divorce in Indonesia and Tunisia, explain the importance of applying the best interest of the child in post-divorce child custody decisions, and finally assess the responsiveness of child custody provisions after divorce in Indonesia and Tunisia. This research is a qualitative research, with a normative juridical approach. The main sources of data for this research are Law Number 1 of 1974 concerning Marriage jo. Law Number 16 of 2019, Compilation of Islamic Law and Code of Personal Status (CPS). Family law reform in Tunisia is more progressive in ensuring the law is responsive to social change and children's needs. On the other hand, Indonesia still faces challenges in integrating traditional values with modern legal principles. Both countries have the potential to learn from each other, especially in creating a more equitable and child-oriented legal system after divorce. Both countries offer flexibility in addressing social contexts, relationships between children and parents, and emotional needs. However, implementation varies between the two countries. Islamic law in Indonesia strongly influences child protection, while Tunisia's CPS reforms in the year focused on gender equality.